Risk factors for Staphylococcus aureus bacteremia in patients with rheumatoid arthritis and incidence compared with the general population: protocol for a Danish nationwide observational cohort study - Bente Glintborg; Merete Lund Hetland; Frank Mehnert; Mette Nørgaard; Sabine Sparre Dieperink; Louise Bruun Oestergaard; Thomas Benfield; Andreas Petersen (BMJ Open)
Introduction Staphylococcus aureus bacteremia (SAB) is an invasive infection with high mortality and morbidity. Rheumatoid arthritis (RA) is associated with increased risk of infections due to the disease per se and the use of antirheumatic treatments. Few minor studies have previously investigated risk of SAB in patients with RA and indicated increased risk compared with the general population. This nationwide observational study aims to investigate incidence of and risk factors for SAB in adult patients with RA compared with the general population. The effect of disease characteristics (eg, joint erosions, disease duration and activity), different antirheumatic treatments and smoking on SAB risk will be evaluated.Methods and analysis All adults (>18 years of age) alive and living in Denmark in 1996–2017 will be identified in The Danish Civil Registration System. Incident patients with RA are identified in the Danish National Patient Registry (DNPR) and the nationwide rheumatology registry, DANBIO, in which information on, for example, antirheumatic treatments, disease characteristics and smoking is collected prospectively in routine care. Information on comorbidities, invasive procedures and prescribed drugs are identified in the DNPR and in The Register of Medicinal Product Statistics. Socioeconomic status is evaluated in national registers on income and education. Incident cases of first-time SAB are identified in The Danish National SAB Database. All registers are linked on an individual level by unique civil registration numbers. Incidence rates and incidence rate ratios will be analysed using Poisson regression models and the impact of possible risk factors will be evaluated.Ethics and dissemination All data will be handled in accordance with the General Data Protection Regulation (EU) 2016/679. No ethical approval is necessary in Denmark when handling registry data only. The results will be presented in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology initiative in international peer-reviewed journals and at medical conferences.Trial registration number NCT03908086.